Living Unrelated Versus Related Kidney Transplantation: A 25-Year Experience with 3716 Cases - Simforoosh, Nasser; Basiri, Abbas; Tabibi, Ali; Javanmard, Babak; Kashi, Amir Hossein; Soltani, Mohammad Hossein; Obeid, Khaled (Urology Journal, 2016)
Purpose: To evaluate the results of transplantation from living unrelated donors (LURD) versus living related donors (LRD) with a long term follow-up of 25-30 years. Materials and Methods: From 1984 to 2015, a total of3716 kidney transplantations (411 LRDs and 3305 LURDs) were enrolled to the study. Long-term survival of grafts and patients as well as the association between relation state and patients or grafts surveillance were the outcomes. Results: A total of 3716 live donor kidney transplants (LRD, n = 411; LURD, n = 3305) were carried out over this period. The mean age of donors was 28 ± 54 years in the LURD group and 34.4 ± 11.7 years in LRD (P < . 001), while the mean age of the recipients was 35.6 ± 15.6 years and 27.6 ± 10.1 years for the two groups, respectively. Donor age was the only statistically significant predictor of graft survival rate (hazard ratio = 1.021, 95% confidence interval: 1.012-1.031). Between 1984 and 2015, patient survival and graft survival improved significantly also patient survival and graft survival was similar in LURDs compared with LRDs. Conclusion: It seems that the outcome of LURD and LRD is comparable in terms of patient and graft survival. Therefore, transplants from LURDs may be proposed as an acceptable management for patients with end stage renal disease.